1994
DOI: 10.1042/bj3010193
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6, but not tumour necrosis factor-α, increases lipogenesis in rat hepatocyte primary cultures

Abstract: The Kupffer-cell products interleukin-6 (IL-6) and tumour necrosis factor-alpha (TNF-alpha) have been shown to stimulate hepatic lipogenesis in vivo. Studies were performed to define the direct effects of these cytokines on lipogenesis in primary-culture rat hepatocytes. Hepatocytes were cultured in the presence of IL-6 or TNF-alpha for periods of 24-72 h. IL-6 increased hepatocyte protein content per microgram of DNA. IL-6 also caused a dose- and time-dependent induction of hepatocyte capacity for incorporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 45 publications
2
15
1
Order By: Relevance
“…In this study, we describe the relationship between fasting glucagon and triglyceride concentrations in obese subjects, especially those that had shown IGT. These results are in line with glucagon infusion leading to decreased basal lipid oxidation and enhanced ability of insulin to inhibit lipid oxidation and augment lipid synthesis in classical studies in healthy subjects (36,37). However, IL6 also influenced lipid metabolism (38) and induced hypertriglyceridemia in experimental models.…”
Section: Discussionsupporting
confidence: 75%
“…In this study, we describe the relationship between fasting glucagon and triglyceride concentrations in obese subjects, especially those that had shown IGT. These results are in line with glucagon infusion leading to decreased basal lipid oxidation and enhanced ability of insulin to inhibit lipid oxidation and augment lipid synthesis in classical studies in healthy subjects (36,37). However, IL6 also influenced lipid metabolism (38) and induced hypertriglyceridemia in experimental models.…”
Section: Discussionsupporting
confidence: 75%
“…Kupffer cells are resident macrophages distributed along the liver sinusoid [10]. Kupffer cells of the liver can also secrete cytokines, including tumor necrosis factor-a (TNF-a) and interleukin-6 (IL-6) [11]. Bioactive molecules generated by Kupffer cells and liver endothelial cells in response to varied stimuli have the capacity to contribute to the regulation of hepatic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Kupffer cells of the liver can also secrete cytokines, and it has been found that factors such as TNF-␣ and IL-6 can influence fatty acid metabolism in the liver and dispose to formation of fatty liver (3,7,10). These inflammatory markers can also contribute to risk for CVD (26).…”
Section: Discussionmentioning
confidence: 99%